Manajemen Relasi Cinta Kasih dalam Pendidikan: Studi Pandangan Hamka dalam Tafsir Al-Azhar - Rangkuti, Bima; Akhmad Shunhaji; Muhammad Suaib Tahir (Canonia Religia, 2024)
This article examines the management of the relationship of love in education from Hamka's perspective in his interpretation of Al-Azhar. The study focuses on revealing the forms of managing the educational relationship of love based on Hamka's interpretation of certain verses in the Tafsir Al-Azhar. The research involves literature review using Tafsir Al-Azhar as its data source. The findings indicate that several forms of relationship management according to Tafsir Al-Azhar include: congruent attitudes (QS. An-Nisâ’(4): 63); open self-image (QS. ʻAbasa (80): 1-10); non-dominative actions (QS. Asy-Syuʻarâ’(26): 215); serious responses (QS. Yûsuf (12): 4-5); providing alternative choices (QS. Al-Qashash (28): 27-28); offering acceptance opportunities (QS. Al-Kahfi (18): 60-64); and full sensitivity (QS. At-Taubah (9): 128). Each of these forms of management found is part of the general principles of relationship management based on the elements that serve as indicators of the educational relationship of love itself.